Study on Production of Peg-Pvdf Membrane for Gas Separation - Muhammad Firdauz, Ali Sibramulisi (2012)
Membranes are also now playing a special role in the field of alternative energy, as one of the fundamental parts of gas product purification through the membrane gas separation process technology. In this sense, membrane technology has a potential contribution for a green chemistry locally, safely, simply, efficiently, and as much as an environmentally friendly manner. The separation of gas mixtures with membranes has emerged from being a laboratory curiosity to becoming a rapidly growing, commercially viable alternative to traditional methods of gas separation. The objective of this research is to develop a high performance of polyethylene glycol (PEG) membrane as an additive to the co-polymer polyvinyl difluoride (PVDF) membrane for gas separation mixture. In the study of separation of CO2/N2 using polymeric membrane system, the best balance for selectivity and permeability of the gas separation membrane is the main part that highly considered as achieving better membrane performance. The co-polymer polyvinyl difluoride (PVDF) membrane used was fabricated using 2-10%wt of polyethylene glycol (PEG) polymer and the rest %wt of ethanol. Coating the PVDF membrane will take the 4-6 hours for it to be totally dried based on the correct percentage of the PEG and ethanol as the solvent. The developed membrane is then tested to determine its performance. Proceed to the gas permeation test, CO2 gas is feed and the permeation flux through the prepared membrane was measured at different pressures. The gas permeation experiment is repeated with N2 gas. The results of this work served as a mean in determining the most balance selectivity and permeability to be used for gas separation processes.